Evaluating the Potentiating Effect of Amethocaine on Tropicamide-Induced Mydriasis in Darkly Pigmented Irides, Using Infrared Pupillometry. (January 2014) - Ogun, Olufunmilola A.; Oliver, Jeffrey W.; Ashaye, Adeyinka O.; Ajayi, Benedictus G. K.
Purpose: To determine whether prior instillation of amethocaine would increase the rate and magnitude of tropicamide-induced pupillary dilatation in darkly pigmented irides. Method: A total of 50 healthy Africans aged 18–40 years, with darkly pigmented irides, received a drop of amethocaine in one eye and a drop of placebo in the contralateral eye, followed by two drops of tropicamide in both eyes. Serial pupil diameters were measured using a monocular infrared video pupillometer. Rate of pupillary dilatation was compared in both eyes. Survival statistics were calculated for the time taken to reach a clinically effective dilatation, clinically effective diameter (CED) of 6.0 mm. Results: Mean difference in pupil diameters between amethocaine- and placebo-treated eyes was 0.30 ± 0.09 mm ( P < 0.002). In all, 62% of amethocaine-treated eyes and only 46% of placebo-treated eyes reached the CED. Conclusion: We observed a small but statistically significant potentiating effect of a drop of amethocaine on tropicamide-induced dilatation within 20 minutes.